2020
DOI: 10.3390/polym12051200
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Secondary Caries Using Resin-Based Pit and Fissure Sealants Containing Hydrated Calcium Silicate

Abstract: The objective of this study was to investigate the effects of hydrated calcium silicate filler (hCS) on resin-based pit and fissure sealants’ acid neutralization, calcium ion release, and mechanical and physical properties. To produce the hCS filler, Portland cement (CS) was mixed with distilled water and ground into fine particles. The particles were then mixed with silanized glass filler and added to a photo-activated resin matrix. To evaluate the acid neutralization and calcium ion release properties, the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 52 publications
1
27
0
Order By: Relevance
“…The results showed that, there were significant differences between the sorption values after 14 and 21 days, for both dental sealants. These observations are in addition to the conclusions of other studies on the complete lack of predictability of the time period regarding the water absorption of dental materials [18].…”
Section: Sorption and Solubility Assessmentsupporting
confidence: 73%
See 2 more Smart Citations
“…The results showed that, there were significant differences between the sorption values after 14 and 21 days, for both dental sealants. These observations are in addition to the conclusions of other studies on the complete lack of predictability of the time period regarding the water absorption of dental materials [18].…”
Section: Sorption and Solubility Assessmentsupporting
confidence: 73%
“…Some of the absorbed water act as a plasticizer and affect mechanical properties of resinbased materials. It is observed that the materials with high absorption also have high solubility values at the same measurement interval [9,18,19].…”
Section: Sorption and Solubility Assessmentmentioning
confidence: 94%
See 1 more Smart Citation
“…SHEDs have a high proliferation rate and can differentiate into adipogenic, chondrogenic, myogenic, neurogenic, odontogenic and osteogenic cells in vitro as well as induce formation of dentine and bone in vivo (Miura et al, 2003). SHEDs, neuralcrest-derived stem cells, also express neural cell markers such as nestin, beta III tubulin and GFAP as well as several pluripotent markers including Oct4 and Nanog (Chai et al, 2000;Miura et al, 2003;Yang et al, 2019;Yang et al, 2020b). SHEDs express more osteocyte markers such as ALP, collagen type I and Runx2 than do BM MSCs in vitro.…”
Section: Dental Pulp Mscsmentioning
confidence: 99%
“…SCAPs are optimised for osteogenesis and odontogenesis; regarding that, SCAPs are considered to be odontoblast precursors in vivo (Du et al, 2020;Nada and El Backly, 2018). However, SCAPs are multipotent and give rise to mesenchymal cell lineages such as adipocytes and chondrocytes (Yang et al, 2020b). Taken together, SCAPs will hopefully gain a significant role in tissue repair and regeneration.…”
Section: Dental Pulp Mscsmentioning
confidence: 99%